MicroRNA-mediated regulation of ferroptosis via GPX4: mechanisms and therapeutic opportunities - S Satvika; B Nivedhitha; K Mounish; B Prathamesh; K L Milan; K. M. Ramkumar (Molecular Biology Reports, 2026)

Identification and validation of PANX1 as an inflammasome-related biomarker in gestational diabetes mellitus: insights from machine learning and experimental approaches - Padmanaban M. Abirami; K. L. Milan; M. Anuradha; Kunka Mohanram Ramkumar (Mammalian Genome, 2026)

Photocatalytic and antifouling performance of g-C3N4, CeO2, and ZnO-grafted PVDF/TiO2 nanohybrid membranes: a comparative study - S. Nivedita; M. Induja; Mani Durai; Karthikeyan Manivannan; Vinoth Kumar Raja; Nagaraj Murugan; Dharani Shanmugapriya; Vijayakumar Paranthaman; Amanullah Fatehmulla; Ramkumar Vanaraj; Paskalis Sahaya Murphin Kumar (Environmental Geochemistry and Health, 2026)

Modulating IL-1β-induced pro-atherogenic endothelial responses through drug repurposing - Kundan Solanki; Sk Rameej Raja; Sunanda Samanta; P. S. Shishira; Anjali Roy; Parimal Kar; Swati Biswas; K. M. Ramkumar; Mirza S. Baig (Inflammopharmacology, 2026)

Tectono-climatic controls on episodic paleosurface development in the Cauvery Basin, Southern India: Implications for basin-scale landscape dynamics - AL Fathima; M. Ramkumar; K. Balasubramani; P.D. Roy; Pankaj Kumar; R. Nagarajan; S. Rajveer (Rhizosphere, 2026)

First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Role of inflammasomes in diabetes mellitus: mechanisms, complications, and therapeutic potential - K. L. Milan; Bhatnagar Megha; K. M. Ramkumar (Molecular Biology Reports, 2025)

Identification of GPX3 as a key biomarker of placental ferroptosis in gestational diabetes mellitus via bioinformatics and clinical analysis - Padmanaban M. Abirami; K. L. Milan; M. Anuradha; Kunka Mohanram Ramkumar (Molecular Diversity, 2025)

Nanoemulsified formulation of cell-free supernatant from Photorhabdus luminescens as a sustainable biopesticide against Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - V.P. Krithika; Anita Bellie; Ramkumar Haran; Deeikshana Thirunavukarasu; Shandeep Ganeshan; C. Sankaranarayanan; Prabhu Somasundaram; M. Suganthy; Gomathi V (Crop Protection, 2025)

Climate Change Impact on Geographical Region and Healthcare Analysis Using Deep Learning Algorithms - Ganduri Srikanth; Ch V. Raghavendran; M. Ramkumar Prabhu; Marepalli Radha; N. V. Siva Kumari; Sabitha Kumari Francis (Remote Sensing in Earth Systems Sciences, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Symbiosis in Sea Anemones: A Few Case Reports Along the Bay of Bengal Large Marine Ecosystem - L. Ranjith; R. Saravanan; S. Ramkumar; C. Kalidas; R. Vinothkumar; D. Linga Prabu; M. Kavitha; A. Mathan Babu; R. Kalaibharathi; P. S. Asha (Marine Ecology, 2025)
The most well‐known relationship is between sea anemones and decapod crustaceans, of which crabs are classic examples of mutualistic interactions in which both organisms benefit from living with zooxanthellae and hermatypic or reef‐forming corals. A marine ecology study off the southern coast of Tamil Nadu revealed five types of sea anemones that cohabit symbiotically with other marine animals. These species include Stichodactyla haddoni (Saville‐Kent, 1893), Entacmaea quadricolor (Leuckart in Ruppell and Leukart, 1828), Radianthus (= Heteractis ) magnifica (Quoy and Gaimard, 1833), Radianthus (= Heteractis ) crispa (Ehrenberg, 1834), and Calliactis polypus (Forsskal, 1775), are found in symbiotic associations. This observation revealed that the decapod porcelain crab Neopetrolisthes is associated with the sea anemones Radianthus and Entacmaea , whereas this has not been reported in Stichodactyla . The hermit crab anemone, C. polypus , is generally associated with hermit crabs, and we report this association for the first time in live gastropod, Turbinella pyrum (Linnaeus, 1767). A few animals (both the host and symbiont) were brought to the cnidarian laboratory at the ICAR‐Tuticorin Regional Station of the CMFRI, where they were maintained in optimum seawater for further observations. The present study aimed to compare previous reports of symbiosis in decapod crustaceans and gastropods with sea anemones from Indian waters to provide insight into the dynamics of symbiosis in the Bay of Bengal Large Marine Ecosystem.

Diffusion of organochlorine (OCPs) and cypermethrin pesticides from rohu (Labeo rohita) internal organs to edible tissues during ice storage: a threat to human health - Ulaganathan Arisekar; Robinson Jeya Shakila; Rajendran Shalini; Balasubramanian Sivaraman; Arjunan Karthy; Mysoon M. Al-Ansari; Nora Dahmash Al-Dahmash; R. Mythili; Woong Kim; Sugumar Ramkumar; Bhagyalakshmi Kalidass; Shannon N. Sangma (Environmental Geochemistry and Health, 2024)

Developments in analytical techniques for chemostratigraphy, chronostratigraphy, and geochemical fingerprinting studies: Current status and future trends - Balaram V; Ramkumar M; Akhtar R. Mir (Journal of South American Earth Sciences, 2023)

Ensemble classifier fostered detection of arrhythmia using ECG data - M. Ramkumar; Manjunathan Alagarsamy; A. Balakumar; S. Pradeep (Medical & Biological Engineering & Computing, 2023)

Recent insights on tea metabolites, their biosynthesis and chemo-preventing effects: A review - Ramkumar Samynathan; Muthu Thiruvengadam; Shivraj Hariram Nile; Mohammad Ali Shariati; Maksim Rebezov; Raghvendra Kumar Mishra; Baskar Venkidasamy; Sureshkumar Periyasamy; Ill-Min Chung; Mirian Pateiro; José M. Lorenzo (Critical Reviews in Food Science and Nutrition, 2023)

Geochemical fractionation, mobility of elements and environmental significance of surface sediments in a Tropical River, Borneo - R. Nagarajan; Sellappa Gounder Eswaramoorthi; A. Anandkumar; M. Ramkumar (Marine Pollution Bulletin, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Pigment composition analysis of fruit pulp in the recombinant progenies reveals the polygenic nature of pulp color inheritance in guava (Psidium guajava L.) - Madhubala Thakre; Hanamant S.; Ramkumar M.K.; Rutuparna Senapati; Shalini Gaur Rudra; Supradip Saha; A. Nagaraja; M. K. Verma; Gopala Krishnan S.; Eldho Varghese; Amitha Mithra Sevanthi (Tree Genetics & Genomes, 2023)

Sustainable approach to manage the vulnerable rodents using eco-friendly green rodenticides formulation through nanotechnology principles – A review - S. Karthick Raja Namasivayam; Subramanian Srinivasan; Krishnappa Samrat; Bala Priyalakshmi; Ramkumar Dinesh Kumar; Arvind Bharani; Ramkumar Ganesh Kumar; M. Kavisri; Meivelu Moovendhan (Process Safety and Environmental Protection, 2023)

Observations and mesoscale forecasts of the life cycle of rapidly intensifying super cyclonic storm Amphan (2020) - Jyoti Bhate; Amit Kesarkar; Arpita Munsi; Kasturi Singh; Asish Ghosh; Abhishek Panchal; Ramkumar Giri; M. M. Ali (Meteorology and Atmospheric Physics, 2023)

Comparative assessment of leaf photosynthetic traits for improved carbon dioxide fixation in selected tree species of Pachamalai hills - Suganthi Kanagaraj; Maniraj Rathinam; M. K. Ramkumar; Rohini Sreevathsa; Govindaraju Munisamy (Brazilian Journal of Botany, 2023)

Nanoparticle assorted biofuels production from biowastes through transesterification - T. Sathish; R. Saravanan; M. Rajasimman; Ayman A. Ghfar; Vanaraj Ramkumar (Fuel, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Genetic diversity analysis of wild and cultivated Rosa species of India using microsatellite markers and their comparison with morphology based diversity - Abhay Kumar Gaurav; Namita; D. V. S. Raju; M. K. Ramkumar; M. K. Singh; Bhupinder Singh; S. Gopala Krishnan; Sapna Panwar; Amitha Mithra Sevanthi (Journal of Plant Biochemistry and Biotechnology, 2022)

Allele mining for a drought responsive gene DRO1 determining root growth angle in donors of drought tolerance in rice (Oryza sativa L.) - Bablee Kumari Singh; M. K. Ramkumar; Monika Dalal; Archana Singh; Amolkumar U. Solanke; Nagendra K. Singh; Amitha Mithra Sevanthi (Physiology and Molecular Biology of Plants, 2021)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

Smartphone geospatial apps for dengue control, prevention, prediction, and education: MOSapp, DISapp, and the mosquito perception index (MPI) - A. N. Babu; E. Niehaus; S. Shah; C. Unnithan; P. S. Ramkumar; J. Shah; V. V. Binoy; B. Soman; M. C. Arunan; C. P. Jose (Environmental Monitoring and Assessment, 2019)

Morphological Deformities in Neotrygon kuhlii (Muller & Henle, 1841) from Gulf of Mannar, Bay of Bengal, India - L. Ranjith; R. Saravanan; C. Kalidas; M. Kavitha; S. Ramkumar; K. K. Joshi; P. P. Manojkumar (Thalassas: An International Journal of Marine Sciences, 2019)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Comprehensive studies of hydrogeochemical processes and quality status of groundwater with tools of cluster, grouping analysis, and fuzzy set method using GIS platform: a case study of Dalcheon in Ulsan City, Korea - S. Venkatramanan; S. Y. Chung; R. Rajesh; S. Y. Lee; T. Ramkumar; M. V. Prasanna (Environmental Science and Pollution Research, 2015)

Nucleotide variation and identification of novel blast resistance alleles of Pib by allele mining strategy - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; M. S. Prasad; V. Ravindra Babu (Physiology and Molecular Biology of Plants, 2015)

A spatially explicit data-driven approach to assess the effect of agricultural land occupation on species groups - Pieter M. F. Elshout; Rosalie van Zelm; Ramkumar Karuppiah; Ian J. Laurenzi; Mark A. J. Huijbregts (The International Journal of Life Cycle Assessment, 2014)

Speciation of selected heavy metals geochemistry in surface sediments from Tirumalairajan river estuary, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; M. P. Jonathan (Environmental Monitoring and Assessment, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

The molecular diversity and evolution of Rice tungro bacilliform virus from Indian perspective - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; B. Sailaja; Jagrati Singh; G. Ramkumar; D. Krishnaveni; S. M. Balachandran (Virus Genes, 2012)

Genetic variation of coat protein gene among the isolates of Rice tungro spherical virus from tungro-endemic states of the India - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; G. Ramkumar; D. Krishnaveni; C. N. Neeraja; M. Sheshu Madhav; D. Ladhalakshmi; S. M. Balachandran; B. C. Viraktamath (Virus Genes, 2012)

Persistence and Dissipation Kinetics of Deltamethrin on Chili in Different Agro-Climatic Zones of India - Suneet Pandher; S. K. Sahoo; R. S. Battu; Balwinder Singh; M. S. Saiyad; A. R. Patel; P. G. Shah; C. Narendra Reddy; D. Jagdishwar Reddy; K. Narasimha Reddy; Ch. Sreenivasa Rao; Tirthankar Banerjee; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Alterations in inheritance pattern and level of cytosine DNA methylation, and their relationship with heterosis in rice - K. Sakthivel; K. Girishkumar; G. Ramkumar; V. V. Shenoy; S. T. Kajjidoni; P. M. Salimath (Euphytica, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Genetic regulation of amniotic fluid TNF-alpha and soluble TNF receptor concentrations affected by race and preterm birth - Ramkumar Menon; Digna R. Velez; Nicole Morgan; Salvatore J. Lombardi; Stephen J. Fortunato; Scott M. Williams (Human Genetics, 2008)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

Barium anomaly preceding K/T boundary: possible causes and implications on end Cretaceous events of K/T sections in Cauvery basin (India), Israel, NE-Mexico and Guatemala - M. Ramkumar; M. Harting; D. Stüben (International Journal of Earth Sciences, 2005)